Assessment of Urban Noise in School Environments - Case Study in Batu Pahat, Johor - Ghing, Tong Yean; Teng, Toh Yoke; Seyed Hakim, Seyed Jamalaldin; Sali, James Uleh; Ewon, Udom (International Journal of Integrated Engineering, 2023)
In recent decades, urban noise has become well-known as one of the critical problems affecting the quality of life in urban areas around the world. Noise assessment is becoming more common in Malaysia as many cities in this country become highly populated and industrialized with serious noise pollution issues, particularly in schools. The aims of this study are to identify the factors and effects of noise in the school environments and evaluate the acoustic comfort of the teachers during the teaching lesson in the school environment. A total of 3 schools located in the urban area of Batu Pahat, Johor, which were Sekolah Menengah Kebangsaan (SMK), Tinggi Batu Pahat, SMK Tun Aminah and SMK Semerah were chosen as study areas. In the present study, questionnaires survey using Google Form were distributed to teachers working in the selected schools. Expert reviews and a pilot study were carried out before the actual survey. The results indicated that the noise factors were coming from inside and outside the classroom, mainly from traffic noise and heavy vehicles near the school environment and noise from student activities and chattering. Teachers need to raise their voice during the teaching and learning process, and some of them had a sore throat.  SMK Tinggi Batu Pahat and SMK Tun Aminah teachers were uncomfortable with the existing acoustic comfort of the school environments.